Building Value Co-creation, Brand Loyalty, and Brand Trust Through Social Media Marketing - Al Hazmi, Muhammad Zaky Afkar; Muhammad, Yusuf; Pangestuti, Irene Rini Demi (Research Horizon, 2024)
This study aims to analyse the influence of social media marketing on brand loyalty, brand trust, and value co-creation in the business of fresh fish stock providers based in Semarang City and Semarang Regency. Additionally, this study examines the level of public interest in fish consumption, which serves as a form of support for the government's initiative to promote fish consumption. This study uses the AMOS Structural Equation Modelling (SEM) analysis method. This study involved 383 respondents. The results of this study show that social media marketing has a significant influence on brand loyalty, brand trust, and value co-creation. Additionally, brand trust and brand loyalty have also been proven to have a significant influence on value co-creation. The findings of this research will offer fresh perspectives on the significance of social media marketing in fostering trust, loyalty, and customer engagement in value co-creation, particularly in the fresh fish sales industry. This knowledge can enhance marketing strategies and bolster government initiatives aimed at boosting fish consumption among Indonesians.